ChemInform Abstract: Ruthenium and Osmium Complexes Containing 2‐(Aminomethyl)pyridine (Ampy)‐Based Ligands in Catalysis. Issue 51 (December 2015) - Chelucci, Giorgio; Baldino, Salvatore; Baratta, Walter
Abstract: Review: 150 refs.